2010
DOI: 10.1038/modpathol.2009.195
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of telomere length shortening with promoter methylation profile of p16/Rb and p53/p21 pathways in breast cancer

Abstract: Unregulated cell growth, a major hallmark of cancer, is coupled with telomere shortening. Measurement of telomere length could provide important information on cell replication and proliferation state in cancer tissues. Telomere shortening and its potential correlation with downregulation of cell-cycle regulatory elements were studied by the examination of relative telomere length and methylation status of the TP53, P21 and P16 promoters in tissues from breast cancer patients. Telomere length was measured in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…To our knowledge, this is the first report to specifically assess telomere lengths in archived clinical ILC specimens by telomere-specific FISH. Three previous studies have analyzed small subsets of ILC cases using different methodologies to assess telomere length/content; telomere restriction fragment analysis by Southern blotting [24], slot blot titration assay [16], and quantitative polymerase chain reaction [25]. These previous reports, which relied on measurements of average telomere lengths obtained from DNA samples purified from bulk tumor tissue samples, did not observe a statistical difference in telomere lengths between invasive ductal and lobular carcinomas.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this is the first report to specifically assess telomere lengths in archived clinical ILC specimens by telomere-specific FISH. Three previous studies have analyzed small subsets of ILC cases using different methodologies to assess telomere length/content; telomere restriction fragment analysis by Southern blotting [24], slot blot titration assay [16], and quantitative polymerase chain reaction [25]. These previous reports, which relied on measurements of average telomere lengths obtained from DNA samples purified from bulk tumor tissue samples, did not observe a statistical difference in telomere lengths between invasive ductal and lobular carcinomas.…”
Section: Discussionmentioning
confidence: 97%
“…[42][43][44][45] Alternatively, there is an acute DNA-repair related event after Tet1 overexpression, which triggers the phosphorylation and up-regulation of p53 as p53 is quickly up-regulated after DNA damage triggered by UV or ionizing irradiation. 46 base excision repair was shown to be required for the completion of TET-mediated demethylation process, 29 48 49 we decided to check the association of p53 increase with DNA-damage signaling pathways.…”
Section: Phospho-p53 (Ser15) Is Elevated By Dna-pk Phosphorylation Inmentioning
confidence: 99%
“…Unfortunately, the comparison of our data on the hypermethylation in the promoters of p14 ARF , p16 INK4a , and ATM from the impalpable lesions and the corresponding fluids (blood and saliva) with the data from other publications [11,[26][27][28][29][30][31][32] is not possible due to differences in the applied methodology. Besides, most of our patients are exposed to social and economic conditions of stress and other variables intrinsic to the environment contributing to tumor development, which may explain in part the rates presented here.…”
Section: Discussionmentioning
confidence: 87%
“…They demonstrated that the shortening of the telomere length is correlated with the hypermethylation in p16 INK4a , leading to genomic instability [30]. The hypermethylation of p16 INK4a in the blood was detected in 22%, compared with 1.3% in controls [28].…”
Section: Discussionmentioning
confidence: 98%